Morphological analysis of adsorbent based on empty fruit bunch-reduced graphene oxide reinforced with chitosan - Raman, M. (Institute of Electrical and Electronics Engineers Inc., 2021)
Environmental pollutions such as poisoning of water sources with heavy metals are a huge concern due to its implications to environment, economy, society, and health. Currently available techniques such as ion exchange, electrodeposition, chemical precipitation, mechanical filtration, and selective liquid-liquid extraction is expensive and not environmentally safe. The usage of empty fruit bunch (EFB) as an adsorbent will be an attractive solution as it is the most abundant residues of oil palm plantation. Although it is being widely used for the removal of heavy metals, the drawbacks such as disposal difficulties and high operational cost severely limits its usability. In this study, empty fruit bunch (EFB) will be combined with reduced graphene oxide (rGO) and chitosan via lyophilization technique to form a composite as an adsorbent. Empty fruit bunch (EFB) will undergo alkaline-oxidative pretreatment to combine with reduced graphene oxide (rGO) and chitosan to form an adsorbent in the form of powder via lyophilization technique. Empty fruit bunch (EFB) will be characterized by SEM, FESEM analysis to study the changes on morphology of the adsorbent. The proposed composite has good potential as it will be lightweight, low-cost, and contributes to the current expectations of circular economy. Â© 2021 IEEE.